Health Safety and Environmental Hazards of the Chlorination Unit of Combined Cycle Power Plants by Using HAZOP and Bow-Tie Methods - Hasti Borgheipour; Ghazaleh Monazami Tehrani; Nadia Abbaszadeh Tehrani; Saeed Nasiri Lomer; Azadeh NEKOOEI ESFAHANI; Iraj MOHAMMADFAM (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Power plants are considered as the most important infrastructure for economic development. Risk assessment and risk management in these industries is essential to prevent accidents in these type of industries. The purpose of this study was to identify and evaluate the health safety and environmental hazards of the chlorination unit of combined cycle power plants by using HAZOP and Bow-Tie methods. Methods: In this study, the hazards of chlorine production in different parts of the chlorination unit were identified using the HAZOP method. After assessing the hazards, the scenario of converting high risk into critical events was developed. Finally, the Bow-Tie method was used to assess the selected critical event. Resulting: 7 top events and 105 risk cases were identified in the chlorination unit of the studied plant by using HAZOP method.  The results showed that 65% of identified risks were acceptable and 14% related to the undesirable risks. The risk of the Chlorine Reservoir explosion related to high hydrogen pressure with regard to identified threats and also its financial, environmental and personal injuries consequences was determined as the most important top event. Therefore this event was analyzed by Bow-Tie and risk prevention measures were proposed. Conclusion: Using the combined method to identify and analyze the hazards showed the effectiveness of these methods together. Also, choosing the appropriate methods to overlap the strengths and weaknesses of each method can lead to an optimal outcome in risk management.